COVID-19 and the Growth Potential - Michael Grömling (Intereconomics, 2021)
The lasting economic impact of the coronavirus pandemic will become apparent in the development of the macroeconomic factors of production – labour, capital, human capital as well as the stock of technical knowledge. Changes in behaviour such as a greater acceptance of technology can strengthen potential output permanently. By contrast, negative effects may arise from growing protectionist attitudes or long-lasting uncertainties and 'scarring effects'. In any case, the coronavirus crisis has induced a technology push. This may be intensified if digitisation gains additional support from investments in infrastructure or if the pandemic heralds a renaissance in the natural sciences – with a corresponding impact on human and physical capital as well as on technical knowledge. For the time being, it is unclear what effects the restructuring and secular structural change will have on potential output. However, dangers are lurking in the acceleration of geopolitical tensions, a misunderstanding of technological sovereignty and increasing government interventions, which, as a whole, could hamper innovation and investment.
Keywords: 330; Coronavirus; Technischer Fortschritt; Digitalisierung; Wirtschaftswachstum; Deutschland